A Semi-Supervised Framework for MMMs-Induced Fuzzy Co-Clustering with Virtual Samples. (23rd June 2016) - Tanaka, Daiji; Honda, Katsuhiro; Ubukata, Seiki; Notsu, Akira
Abstract : Although the goal of clustering is to reveal structural information from unlabeled datasets, in cases with partial structural supervisions, semi-supervised clustering is expected to improve partition quality. However, in many real applications, it may cause additional costs to provide an enough amount of supervised objects with class labels. A virtual sample approach is a practical technique for improving classification quality in semi-supervised learning, in which additional virtual samples are generated from supervised objects. In this research, the virtual sample approach is adopted in semi-supervised fuzzy co-clustering, where the goal is to reveal object-item pairwise cluster structures from cooccurrence information among them. Several experimental results demonstrate the characteristics of the proposed approach.